Colorimetric Detection of Heavy Metal Ions Using Green Synthesized Silver Nanoparticles from Kaempferia Galanga Rhizomes Extract - Muhammad, Nurul Nadia (Universiti Sains Malaysia, 2022)
Green synthesis of silver nanoparticles (AgNPs) is a vast developing area of research due to its cost-effectiveness and environmental friendliness. In this study, silver nanoparticles (AgNPs) were rapidly synthesized by treating silver ion (Ag+ ion) through a simple and green route using Kaempferia galanga rhizome extract which can act simultaneously as a reductant and stabilizer. The colour of AgNPs solutions were observed and UV-Vis spectroscopy was used to validate the presence of AgNPs in the solution. The result shows that 4% (w/v) of plant extract, 0.01 M concentration of silver nitrate (AgNO3), 72 hours incubation time and 1:3 ratio of plant extract to AgNO3 are the most suitable concentration where the colour of solution change from pale yellow to dark brown and UV-Vis spectroscopy showed a peak in the range of 400-500 nm which is the typical absorption spectrum of AgNPs. Then, characterization of AgNPs was done using Scanning Electron Microscope (SEM) and energy dispersive X-ray (EDX) where a spherical shape can be seen and more than 58 % weight of silver particles were detected to be in the solution. The synthesized AgNPs were used for colorimetric detection of 12 types of heavy metal ions, namely Mn2+, Ni2+, Zn2+, Co2+, Fe3+, Fe2+, Al3+, Cr3+, Cd2+, Pb2+, Hg2+, and Cu2+ with 1 mM concentration and the results showed a colour discoloration ranging from brownish to greenish for Fe2+ while no obvious colour changes for other heavy metal ions. The UV-Vis spectra also show obvious peak changes for Fe2+, Fe3+ and Hg2+. Further testing was carried out to detect the sensitivity of the synthesize AgNPs towards the selected heavy metal ions in lower concentration. No obvious changes in colour of solution for all three heavy metal ions were observed but UV-Vis spectra shows that 0.4 mM was the lowest concentration that are able to be detect by the AgNPs.